Solvent Effect on Morphology and Optical Properties of Poly(3-hexylthiophene):TIPS-Pentacene Blends - Ozório, Maíza Silva [UNESP]; Camacho, Sabrina Alessio [UNESP]; Cordeiro, Neusmar Junior Artico; Duarte, José Leonil; Alves, Neri [UNESP] (Springer Nature, 2018)
Optical, electrical, and morphological properties of poly(3-hexylthiophene):6,13-bis(triisopropylsilylethynyl) (TIPS)-pentacene (P3HT:TP) blend films, in the proportion of 1:1 (w/w), have been investigated using chloroform, toluene, or trichlorobenzene as solvent. The main morphological feature was formation of aggregates that tended to segregate vertically, exhibiting characteristics that were strongly influenced by the type of solvent applied. The phase segregation of TP observed for the P3HT:TP blend film obtained using chloroform, the most volatile of the investigated solvents, can be explained based on the Marangoni effect and the Flory–Huggins model. The TP molecules induce better organization of P3HT, as evidenced by the ultraviolet–visible (UV–Vis) absorption spectra. Photoluminescence (PL) measurements revealed quenching and an increase in the lifetime of the carriers. The PL measurements also showed that the exciton dissociation was dependent on the characteristics of the surface on which the film was deposited. P3HT:TP blend film prepared using trichlorobenzene showed the best morphology with moderate phase segregation and better P3HT ordering. The output current from organic field-effect transistors (OFETs) with blend film prepared using trichlorobenzene was three times (3×) larger than when using the other solvents, with carrier mobility of 5.0 × 10−3 cm2 V−1 s−1.
Keywords: morphology; optical properties; Semiconductor blend; TIPS-pentacene; vertical segregation